Effect of Okra Fruit (Abelmoschus esculentus) Extract on Adenocarcinoma Mammae by Assessing Caspase-3 Expression and Apoptosis Index: An In Vivo Study - Satrio Putra Prawiro; Selamat Budijitno; Trilaksana Nugroho; Nani Maharani; Eriawan Agung Nugroho (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Background: Breast cancer is cancer in women with the highest incidence. Adriamycin-cyclophosphamide (AC) chemotherapy is a breast cancer therapy with good efficacy, but its effectiveness has not been maximized. The okra fruit extract is known to have anti-cancer effects from lectins, so it can be used as a complementary chemotherapy therapy to increase effectiveness with minimal side effects. Methods: This study is an experimental study using female rats Sprague Dawley strain, aged 4 weeks, were induced by DMBA to form mammary adenocarcinoma cells. Divided into groups; control (K): no treatment, treatment 1 (P1): AC chemotherapy (adriamycin 1.5 mg/time and cyclophosphamide 15 mg/time), treatment 2 (P2): okra extract 150 mg/kgBW/day, and treatment 3 (P3): combination of AC and okra extract. Results: The highest levels of caspase-3 and apoptosis index were found in the P3 group at 39.66±1.78 and 20.93±1.67, respectively. Giving green okra extract to chemotherapy agents can increase the anti-cancer effect by increasing the apoptosis index and caspase-3 levels significantly (p<0.05) compared to other groups. Conclusion: Okra fruit extract was able to increase the apoptosis response to adriamycin-cyclophosphamide chemotherapy in vivo, as indicated by the high expression of caspase-3 and apoptosis index.